Pengaruh Belanja Online terhadap Perilaku Komsumtif pada Mahasiswa di Kota Medan - Didi Haryadi; Dwita Anggriani Sitorus; Esra Fania Silitonga (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines how online shopping contributes to the development of consumptive behavior among university students in Medan, emphasizing the role of digital platforms, promotional strategies, and psychological drivers that influence purchasing decisions. The results show that students increasingly engage in online transactions due to ease of access, persuasive product visuals, and continuous exposure to promotional content that stimulates emotional and impulsive responses. External factors such as live commerce, influencer endorsements, integrated marketing communication, and financial technology services further reinforce students’ purchase intentions by creating a seamless and appealing digital shopping environment. The findings indicate that repetitive purchases often arise not from genuine needs but from stimuli such as attractive discounts, aesthetic product displays, and the convenience of digital payment systems. The study also highlights that self-control becomes a key moderating factor in managing impulsive tendencies triggered by online shopping features. These insights underscore the need for stronger digital literacy and financial awareness so that young consumers can make more rational decisions and avoid excessive spending patterns shaped by online marketplaces.